Berkumur larutan madu hutan 15% efektif mengurangi jumlah koloni bakteri dalam saliva Gargling 15% wild honey solution effective in reducing the number of bacteria colonies in saliva - Irfan Sugianto; M. Ilyas (Journal of Dentomaxillofacial Science, 2013)
The use of natural mouthwash has been developed; honey is one of them. In the Holy Qur'an has mentioned that honeyis the recommended drug for treating various diseases. Honey has anti-bacterial, anti-fungal and anti-oxidant effects.This study aims to determine the effectiveness of wild honey solution 15% to the number of colonies of bacteria insaliva. In the quasi-experimental research design with pre and posttest design with control group, the samples weredivided into two groups. Group 1 is the group that rinsing with a solution of wild honey, and group 2 as the control,gargling with mouthwash containing 1% povidone iodine. The results showed that in group 1, the average number ofbacterial colonies was 233.3 CFU/ml before rinsing to 183.8 CFU/ml after rinsing (p<0.05). It is concluded thatrinsing with a solution of 15% wild honey effectively reduce the number of colonies of bacteria in saliva.